Diagnosis and management of junctional ectopic tachycardia in children - Sasikumar, Navaneetha; Kumar, Raman; Balaji, Seshadri (Annals of pediatric cardiology, 2021)
Junctional ectopic tachycardia (JET) is more common in its postoperative form. A thorough understanding of its etiology, pathophysiology, and management strategies is essential. Classically, postoperative JET is considered to arise from surgical trauma. Genetic susceptibility and an intrinsic morphologic/functional defect in the conduction system inherent in congenital heart diseases likely play a significant role. The devastating effects on postoperative hemodynamics warrant prompt attention. A multipronged management approach with general measures, pharmacotherapy, and pacing has decreased morbidity and mortality. Amiodarone and procainamide remain the preferred drugs, while ivabradine appears promising. Carefully planned randomized trials can go a long way in developing a systematic management protocol for postoperative JET.